Intestinal Form of Human Coronavirus 229E Plays No Role in Peritoneal Sclerosis Pathology in Dialysis Patients - Sirwan Sleman (Advances in Virology)
Infectious peritonitis is found to be a leading factor in the development of viral peritonitis (VP) and encapsulating peritoneal sclerosis (EPS) in patients undergoing peritoneal dialysis (PD) treatment. Bacterial and fungal infections are a major cause of peritonitis in PD patients. Viral infections have rarely been reported in association with peritonitis in PD patients; about 20% of cases are fungal and bacterial culture-negative (so-called sterile peritonitis). Several possible viral causes are reported to cause peritonitis, Coronaviruses are an important virus group that has been found to cause peritonitis in animals (cats), although in human beings these viruses have not been reported to associate with peritonitis. The purpose of this study was to investigate whether the intestinal form of Human 229E coronavirus plays a role in peritonitis and EPS for several peritoneal fluid samples collected from patients with confirmed EPS. Thirty-seven peritoneal fluid samples from 12 patients with histologically confirmed EPS from Manchester University Hospitals were extracted using QIAamp RNA Mini Kit to purify viral RNA. The purified RNA was reverse transcribed and tested using a pan-coronavirus PCR designed to pick up all known human and animal coronaviruses. None of the peritoneal fluid samples was positive, suggesting that active coronavirus infection is not associated with the development of VP in dialysis patients.